Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 27^16 : 9^10
Ta có: (3.9)^16 : 9^10
= 3^16.9^16: 9^10
= 3^16. 9^6
= 3^16.(3^2)^6
=3^16.3^12
=3^28
A= 136.(25+75) - (6.10)2 = 136 . 100 - 602 = 13600 - 3600 = 10000
B= (2.5)3 - {(7.2)2 - 52. [43 : 23 + 112 : 112 - 2(37 -35)]}
=103 - {142 - 52 .[(4:2)3 + (11:11)2 - 2.2]} = 1000 - { 154 - 25 .[8 + 1 -4]} = ....
a) \(A=1+2+2^2+2^3+...+2^{60}\)
=>\(2A=2+2^2+2^3+2^4+...+2^{61}\)
=>\(2A-A=\left(2+2^2+2^3+2^4+...+2^{61}\right)-\left(1+2+2^2+2^3+...+2^{60}\right)\)
=>\(A=2^{61}-1\)
b) \(B=1+3+3^2+3^3+...+3^{46}\)
=>\(3B=3+3^2+3^3+3^4+...+3^{47}\)
=>\(3B-B=\left(3+3^2+3^3+3^4+...+3^{47}\right)-\left(1+3+3^2+3^3+...+3^{46}\right)\)
=>\(2A=3^{47}-1\)
=>\(B=\frac{3^{47}-1}{2}\)
c) \(C=1+5^2+5^4+...+5^{200}\)
=>\(5^2C=5^2+5^4+5^6+...+5^{202}\)
=>\(25C=5^2+5^4+5^6+...+5^{202}\)
=>\(25C-C=\left(5^2+5^4+5^6+...+5^{202}\right)-\left(1+5^2+5^4+...+5^{200}\right)\)
=>\(24C=5^{202}-1\)
=>\(C=\frac{5^{202}-1}{24}\)
a) A = \(1+2+2^2+2^3+...+2^{60}\)
2A = \(2.\left(1+2+2^2+2^3+...+2^{60}\right)\)
2A = \(2+2^2+2^3+2^4+...+2^{61}\)
2A - A = \(\left(2+2^2+2^3+2^4+...+2^{61}\right)\)- \(\left(1+2+2^2+2^3+...+2^{60}\right)\)
A = \(2^{61}-1\)
b)B = \(1+3+3^2+3^3+...+3^{46}\)
3B = \(3.\left(1+3+3^2+3^3+...+3^{46}\right)\)
3B = \(3+3^2+3^3+3^4+...+3^{47}\)
3B - B = \(\left(3+3^2+3^3+3^4+...+3^{47}\right)\)- \(\left(1+3+3^2+3^3+...+3^{46}\right)\)
2B = \(3^{47}-1\)
B = \(\left(3^{47}-1\right):2\)
Tìm x
a.( x - 140 ) : 3 = 27
x - 140 = 27 . 3
x - 140 = 81
x = 221
b.14 - 4 ( x + 1 ) = 10
4 ( x + 1 ) = 14 - 10
4 ( x +1) = 4
x + 1 = 1
x = 0
c. 15 ( 7 - x ) = 15
7 - x = 1
x = 6
d.34 ( x - 3 ) = 0
\(\Rightarrow\) 34 = 0 hoặc x - 3 = 0
1. 34 = 0 ( vô lí )
2. x - 3 = 0 \(\Rightarrow\) x = 3
e. 24 + 6 (3 - x ) = 30
6( 3- x ) = 30 - 24
6( 3 - x ) = 6
3 - x = 1
x = 2
f. x3 + 24 = 51
x3 = 51 - 24
x3 = 27
\(\Rightarrow\)x = 3 ; x = -3
g. ( x- 5 )2 - 5 = 44
( x - 5) 2 = 49
\(\Rightarrow\)x - 5 = 7 hoặc x - 5 = -7
1. x - 5 = 7\(\Rightarrow\)x = 12
2. x - 5 = -7 \(\Rightarrow\)x = -2
h. ( x + 1 )3 - 23 = 4
( x + 1 )3 =27
\(\Rightarrow\) x + 1 = 3 hoặc x + 1 = -3
1. x + 1 = 3\(\Rightarrow\)x = 2
2. x + 1 = -3 \(\Rightarrow\)x = -4
\(A=2^5.5^2-3^2-10\\ \\ A=32.25-9-10=800-9-10\\ \\ A=781\)
\(B=3^3.3^2+2^2+3^2\\ \\ B=3^{3+2}+4+9\\ \\ B=3^5+13=243+13\\ \\ B=256\)